El Estado de Inocencia y la Garantía de la no Autoincriminación en Materia Tributaria: Un Análisis a Partir de la Conexidad Entre el Procedimiento Administrativo y el Proceso Penal - Álvarez Echagüe, Juan Manuel (2014)
In this article, the author attempts to establish the limitations and consequences resulting from the use of evidence that, being obtained from the exercise of the powers of investigation and enforcement that owns the Treasury, then is carried to the tax criminal proceedings, as the basis for the complaint made by the Tax Administration. For this, the author approaches the taxpayer’s right against self-incrimination (or not to incriminate himself ) as well as some general concepts of the state of innocence, and then analyzes how these concepts are related to the tax law, specifically with the evidence inside it. The article also contains a number of ideas that attempts to summarize the thoughts and positions taken on the issue in current doctrine and jurisprudence in Argentina, establishing in turn, parallel situations and comparisons with the Peruvian tax system.